PROBLEMATIKA GURU DALAM MELAKSANAKAN EVALUASI PEMBELAJARAN SISWA DI KELAS IV SEKOLAH DASAR - Aan Mulya Ahmadi; Dhia Raihan; Hadisa Alawiyah; Martines Martines; Agus Kistian (Jurnal Binagogik, 2025)
This study aims to identify the problems faced by teachers in implementing learning evaluation in class IV SD Negeri 1 Mata Ie and find effective solutions. The method used is descriptive qualitative research with data collection techniques through in-depth interviews. The results showed that teachers faced various obstacles, such as differences in students' reading and writing abilities, time constraints, difficulties in designing comprehensive evaluation instruments, and challenges in evaluating inclusive students. The impact of these problems includes less holistic evaluation and decreased student motivation to learn. Collaboration between teachers, parents and support teachers was also identified as an important step to improve the effectiveness of learning evaluation. This research provides recommendations for the development of evaluations that cover cognitive, affective and psychomotor domains more optimally.